Japonica Array NEO with increased genome-wide coverage and abundant disease risk SNPs. (13th May 2021) - Sakurai-Yageta, Mika; Kumada, Kazuki; Gocho, Chinatsu; Makino, Satoshi; Uruno, Akira; Tadaka, Shu; Motoike, Ikuko N; Kimura, Masae; Ito, Shin; Otsuki, Akihito; Narita, Akira; Kudo, Hisaaki; et al.
Abstract: Ethnic-specific SNP arrays are becoming more important to increase the power of genome-wide association studies in diverse population. In the Tohoku Medical Megabank Project, we have been developing a series of Japonica Arrays (JPA) for genotyping participants based on reference panels constructed from whole-genome sequence data of the Japanese population. Here, we designed a novel version of the SNP array for the Japanese population, called Japonica Array NEO (JPA NEO), comprising a total of 666, 883 markers. Among them, 654, 246 tag SNPs of autosomes and X chromosome were selected from an expanded reference panel of 3, 552 Japanese, 3.5KJPNv2, using pairwise r 2 of linkage disequilibrium measures. Additionally, 28, 298 markers were included for the evaluation of previously identified disease risk markers from the literature and databases, and those present in the Japanese population were extracted using the reference panel. Through genotyping 286 Japanese samples, we found that the imputation quality r 2 and INFO score in the minor allele frequency bin >2.5–5% were >0.9 and >0.8, respectively, and >12 million markers were imputed with an INFO score >0.8. From these results, JPA NEO is a promising tool for genotyping the Japanese population with genome-wide coverage, contributing to the development of genetic risk scores. Graphical Abstract: